(untitled) (Research, Society and Development, 2022)
This study is an integrative literature review that aimed to relate the importance of pedagogical practices in Basic Education and their contributions to the ’pedagogical doing’ in the school context. The research locus is mainly based on Cruz (2007), Oliveira (2009), Paro (2009), Santos & Matthiesen (2012) and Brasil (2018), having the BNCC as a guiding document. The results allow us to infer that pedagogical practices are actions that potentiate the teaching and learning processes, especially when the teacher acts as a mediator of knowledge based on the social and regional contexts of students. In Early Childhood Education, pedagogical practices highlight the playful movement and playing, while in Elementary School, the researcher teacher takes action promoting the connection between teaching and research, for the formation of critical and reflective citizens to act in citizenship and the world of work. In addition, Elementary School constitutes an essential stage for the discussion of themes that include body, gender and sexuality in terms of breaking prejudices and raising awareness about cultural plurality. it can be inferred that it is a stage that lacks practices that show diversity, social relations and the development of intellectual autonomy.